The Role of The Industrial Policy in Developing The Algerian Industrial Sector Le Rôle De la Politique Industrielle Dans le Développement Du Secteur Industriel Algérien - Djemai, Samira; Billami, Meryem (Finance and Business Economies Review, 2019)
The study aims to reveal and identify the position of industry in the Algerian economy for its great importance in developing the economic wheel. To fulfill this aim, therefore, data o an economic indicators during 2007-2016 were analyzed to figure their contribution. The results came out that industry has a considerable contribution to the gross domestic product” GDP “and the added value whereas its modest participation in the labor force showed no more than 30%. However, these contributions cannot be considered real because the extractive industry dominates the industrial sector in Algeria and it is considered the mainstay of the Algerian economy, thus it makes it vulnerable to crises due to changes in oil prices.